The Catholic Religion Subject: A Problem or a Challenge? - Iglesias Blanco, Xulio C. (Educación y Futuro: Revista de Investigación Aplicada y Experiencias Educativas, 2020)
This paper sums up classroom experiences based on specific Catholic religion issues of both social and academic nature that our students face. the aim is to contextualise these experiences in order to propose humanizing alternatives. Some paths already used to battle our students' religious indifference are presented here: taking into account the groups of student's reality, being able to "sell" the Catholic religion subject, combatting prejudices, claiming the value of the useless in a materialistic society, translating salvation as happiness, establishing the differences between theory and experience, unveiling the evolution of religious concepts, bringing god back in our lives, demonstrating the personal existence of Jesus of Nazareth, being surprised by the influence of Christianity in our society/city and discovering the religious experience as a deeply human reality.
Keywords: catholic religion subject; secondary school; humanisation; eligious indifference; processes; significance